Arterial stiffening contributes to impairment of cerebrovascular reactivity in patients with coronary artery disease without carotid stenosis - Ručka, David; Marek, Josef; Rücklová, Zuzana; Lubanda, Jean-Claude; Havránek, Štěpán; Škvařil, Jan; Vařejka, Petr; Chochola, Miroslav; Karetová, Debora; Kořínek, Josef; Linhart, Aleš (Physiological research, 2015)
Impaired cerebrovascular reactivity (CVR), an important risk factor for future stroke, is affected by a presence carotid stenosis. However, in some cases CVR can be impaired in the absence of carotid stenosis due to several poorly characterized mechanisms. We hypothesized that arterial stiffening as observed in coronary heart disease (CHD) could be associated with alteration in CVR in CHD patients without carotid stenosis. The study population consisted of patients referred for coronary angiography without significant carotid stenosis (<50 %). CVR was evaluated by breath holding index (BHI) measured with transcranial color code duplex ultrasound. Arterial stiffness was assessed by pulse wave velocity (PWV) measured by the oscillometric method. The extent of coronary atherosclerosis was quantified by Gensini score (GS). Out of 186 subjects, sixty-two patients fulfilled the inclusion and exclusion criteria. BHI decreased with increasing PWV (r = -0.47, p<0.001). Decrease in BHI was significantly inversely associated with GS (r = -0.61, p<0.001). GS was associated with PWV (p<0.001). In conclusion, impaired CVR was associated with increased arterial stiffening in CHD patients in the absence of significant carotid stenosis. Thus, we speculate that increased arterial stiffness may at least partially contribute to the pathophysiology of CVR alteration in coronary artery disease.
Keywords: Blood Flow Velocity; Cerebral Arteries; Vascular Stiffness; tuhost cévní stěny; Humans; lidé středního věku; mozkový krevní oběh; rychlost toku krve; Middle Aged; stenóza arteria carotis; Carotid Stenosis; nemoci koronárních tepen; Cerebrovascular Circulation; Coronary Artery Disease; mužské pohlaví; ženské pohlaví; lidé; Aged; senioři; Male; arteriae cerebrales; Female